Endogenous CCL2 neutralization restricts HIV-1 replication in primary human macrophages by inhibiting viral DNA accumulation. Issue 1 (December 2015) - Sabbatucci, Michela; Covino, Daniela; Purificato, Cristina; Mallano, Alessandra; Federico, Maurizio; Lu, Jing; Rinaldi, Arturo; Pellegrini, Matteo; Bona, Roberta; Michelini, Zuleika; Cara, Andrea; Vella, Stefano; et al.
Abstract Background Macrophages are key targets of HIV-1 infection. We have previously described that the expression of CC chemokine ligand 2 (CCL2) increases during monocyte differentiation to macrophages and it is further up-modulated by HIV-1 exposure. Moreover, CCL2 acts as an autocrine factor that promotes viral replication in infected macrophages. In this study, we dissected the molecular mechanisms by which CCL2 neutralization inhibits HIV-1 replication in monocyte-derived macrophages (MDM), and the potential involvement of the innate restriction factors protein sterile alpha motif (SAM) histidine/aspartic acid (HD) domain containing 1 (SAMHD1) and apolipoprotein B mRNA-editing, enzyme-catalytic, polypeptide-like 3 (APOBEC3) family members. Results CCL2 neutralization potently reduced the number of p24 Gag+ cells during the course of either productive or single cycle infection with HIV-1. In contrast, CCL2 blocking did not modify entry of HIV-1 based Virus Like Particles, thus demonstrating that the restriction involves post-entry steps of the viral life cycle. Notably, the accumulation of viral DNA, both total, integrated and 2-LTR circles, was strongly impaired by neutralization of CCL2. Looking for correlates of HIV-1 DNA accumulation inhibition, we found that the antiviral effect of CCL2 neutralization was independent of the modulation of SAMHD1 expression or function. Conversely, a strong and selective induction of APOBEC3A expression, to levels comparable to those of freshly isolated monocytes, was associated with the inhibition of HIV-1 replication mediated by CCL2 blocking. Interestingly, the CCL2 neutralization mediated increase of APOBEC3A expression was type I IFN independent. Moreover, the transcriptome analysis of the effect of CCL2 blocking on global gene expression revealed that the neutralization of this chemokine resulted in the upmodulation of additional genes involved in the defence response to viruses. Conclusions Neutralization of endogenous CCL2 determines a profound restriction of HIV-1 replication in primary MDM affecting post-entry steps of the viral life cycle with a mechanism independent of SAMHD1. In addition, CCL2 blocking is associated with induction of APOBEC3A expression, thus unravelling a novel mechanism which might contribute to regulate the expression of innate intracellular viral antagonistsin vivo . Thus, our study may potentially lead to the development of new therapeutic strategies for enhancing innate cellular defences against HIV-1 and protecting macrophages from infection.